Deep Sequencing and Molecular Characterisation of BK Virus and JC Virus WHO International Reference Materials for Clinical Diagnostic Use - Sheila Govind; Martin Fritzsche; Adrian Jenkins; Megan H. Cleveland; Peter M. Vallone; Neil Almond; Clare Morris; Neil Berry (Viruses, 2023)
Background: Reactivation of JC and BK polyomaviruses during immunosuppression can lead to adverse clinical outcomes. In renal transplant recipients, BKV-associated nephropathy can result in graft loss, while in patients with autoimmune disorders, prolonged immunomodulatory drug use can cause rare onset of progressive multifocal leukoencephalopathy due to JCV reactivation. In such patients, accurate BK and JC viral load determinations by molecular technologies are important for diagnosis and clinical management; however, comparability across centres requires effective standardisation of diagnostic molecular detection systems. In October 2015, the WHO Expert Committee for Biological Standardisation (ECBS) established the 1st WHO International Standards (ISs) for use as primary-order calibrants for BKV and JCV nucleic acid detection. Two multi-centre collaborative studies confirmed their utility in harmonising agreement across the wide range of BKV and JCV assays, respectively. Previous Illumina-based deep sequence analysis of these standards, however, identified deletions in different regions, including the large T-antigen coding region. Hence, further detailed characterization was warranted. Methods: Comprehensive sequence characterisation of each preparation using short- and long-read next-generation sequencing technologies was performed with additional corroborative independent digital PCR (dPCR) determinations. Potential error rates associated with long-read sequencing were minimised by applying rolling circle amplification (RCA) protocols for viral DNA (circular dsDNA), generating a full validation of sequence identity and composition and delineating the integrity of full-length BK and JC genomes. Results: The analysed genomes displayed subpopulations frequently characterised by complex gene re-arrangements, duplications and deletions. Conclusions: Despite the recognition of such polymorphisms using high-resolution sequencing methodologies, the ability of these reference materials to act to enhance assay harmonisation did not appear significantly impacted, based on data generated by the 2015 WHO collaborative studies, but highlights cautionary aspects of IS generation and commutability for clinical molecular diagnostic application.